The Effectiveness of Grammarly in Enhancing Grammatical Competence Among First-Year Preservice English Teachers - Irwan, Dedi; Alisa, Alisa; Rada, Devita; Melianti, Dewi; Lestari, Sri (Jurnal Pendidikan Bahasa, 2024)
This study aims to examine the effectiveness of using Grammarly in enhancing the grammatical competence of first-semester students in the English Education Program at Universitas PGRI Pontianak. The research employs an experimental method with a pretest-posttest design. The population consists of 160 first-year prospective English teachers, divided into four classes (A to D). The sample, Class A morning, was selected through cluster random sampling after ensuring that all classes were statistically homogeneous in terms of initial ability. Data analysis was conducted using a paired sample t-test via SPSS. The results indicate that the use of Grammarly as an AI-based learning tool significantly improves students' grammatical competence, with a significance value of 0.02 (p < 0.05). These findings suggest that Grammarly can serve as an effective learning support tool to enhance grammatical proficiency in the context of English language education.